Various Textiles-Based Comparative Analysis of a Millimeter Wave Miniaturized Novel Antenna Design for Body-Centric Communications. (2nd August 2021) - Monirujjaman Khan, Mohammad; Islam, Kaisarul; Shovon, Md. Nakib Alam; Masud, Mehedi; Baz, Mohammed; AlZain, Mohammed A.
Abstract : A 60 GHz compact and novel shaped microstrip-fed antenna based on a textile substrate for body-centric communications has been proposed in this paper. The antenna has a partial ground, and the textile substrate is made up of 1.5 mm thick 100% polyester. Two rectangular sections from the patch antenna's radiator were removed to give the antenna a swan-shaped appearance. The antenna was designed and simulated using computer simulation technology (CST) microwave studio software. Simulated results show that, in free-space, the antenna achieved a high bandwidth of 11.6 GHz with a center frequency of 60.01 GHz. With 89.4% radiation efficiency, the maximum gain of the antenna was 8.535 dBi. For the on-body scenario, the antenna was simulated over five different distances from a human torso phantom. At the closest distance from the phantom, the antenna's gain was 5.27 dBi, while the radiation dropped significantly to 63%. The highest bandwidth of 12.27 GHz was attained at 8 mm, while the lowest bandwidth of 5.012 GHz was attained at 4 mm away from the phantom. Gain and radiation efficiency were comparable to free-space results at the furthest distance. The antenna was also simulated with ten different textile substrates for both free-space and on-body scenarios. Among these ten substrates, denim, tween, and Quartzel fabric had similar performance results as polyester. This design achieved similar performance compared to other 60 GHz textile antennas while being a bit more compact. This antenna will be a promising choice for body-centric communications because of its compact size, textile-based substrate, and excellent on-body performance.